Letter to the editor in response to: COVID-19 pandemic and challenges for socio-economic issues, healthcare and national programs in India (Gopalan and Misra) (2020)
Article by Gopalan and Misra is very informative and covers the current challenges arising due to COVID19. Further, authors has attempted to explore the various socioeconomic and medical aspects affected during this COVID-19 pandemic. It starts with the economic issues, social impacts, cultural influences, and the health related national programs which are regularly getting impacted owing to the ongoing epidemic. The paper throws light on how the pandemic has strongly affected the jobs, businesses transportation, travel, and other sectors which ultimately influence the social-economic balance of the society. This has further led to the decrease in the GDP of the country. The daily wagers and the local business personnel are the most affected ones during this period.